Cyber Persona Trap and its Prolonged Alternatives in Contemporary Metaliteracy - Pasopati, Rommel Utungga; Rosyadi, Machfianita Mirza Ayu; Noviyanti, Anisa Dinda; Wijaya, Silvia Marta; Mohammed, Khaled Ahmed (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2024)
This article exposes how virtual identity or cyber persona deals with metaliteracy today. While traditional identities show particular social constructions, cyber persona asserts ambiguity of sharing culture between cyberspace and real world. The differences also shift enlightenment in literacy into paradox as a consequence of cyber persona trap. Literacy extends to multiliteracy and metaliteracy that enable further possibilities to blur private and public boundaries through interpretations of information. This also encourages the trend of hoax as mismatch between facts and contexts. Hoax exposes absence of reflection on information, or the absence of literacy, in a sharing culture. If literacy defines reading culture, metaliteracy means interpreting in sharing culture. Nevertheless, the interpretation does not enhance understanding because the information is intended for justification of a single truth. Through qualitative method, the analysis includes how metaliteracy shows paradox rather than congruence between virtual and real world. Continuous understanding becomes an alternative to get into the cyber persona. One information alone is never enough to understand realities. In conclusion, cyber persona enables individuals to extend literacy but with a two-edge of blade; information allows further understanding, but could also be used to justify certain ideological truths.